Safety and Operational Efficiency Analysis of Rope Access Method on Non-Linear Geometrical Structure of Monumen Tugu Reog Ponorogo - Muhammad Fajar Mahmud Ananta; Firman Ardiansyah Ekoanindiyo (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
The construction of the 60-meter high Monumen Tugu Reog Ponorogo by CV Gendhis Multi Karya faces extreme vertical accessibility challenges due to the non-linear curved geometry of the structure (dadak merak and barongan). The use of conventional scaffolding is considered slow, expensive, and poses a high risk of damaging the brass ornaments. This study aims to analyze the comparison of operational effectiveness (time, labor, cost) and occupational safety risk levels between scaffolding and rope access methods using the HIRARC matrix based on AS/NZS 4360:2004. Comparative analysis results show that rope access reduces equipment mobilization time by 87.5% (from 12 days to 1.5 days), saves active labor by 70.0% (from 10 people to 3 people), and cuts operational costs by 70.83% (from IDR 120,000,000 to IDR 35,000,000). The initial risk assessment indicates that all working at height activities fall into the High risk category (scores 10-15). After designing technical mitigation actions including dynamic anchor testing of at least 15kN in accordance with BS EN 795:2012 standards, thick canvas corner protectors, and a maximum wind speed limit of 20 knots (37 km/h), the risk level was successfully reduced to the Low category (residual risk scores 2-3). The implementation of rope access is proven to be the optimal solution that guarantees both safety and productivity aspects in the construction of cultural heritage buildings with complex geometries.